PARADOKS BEZKARNOŚCI PRZESTĘPSTWA SKARBOWEGO - Prusak, Feliks (Zeszyty Prawnicze, 2016)
Paradox Concerning Fiscal Crime Impunity Summary The Penal Fiscal Code allows in some cases criminal impunity when the offender offers a justified correction of his tax declaration and compensates the public law due charge. The analysis concerns the art. 16a of the Penal Fiscal Code considered a lex specialis compared to the art. 16 of the same code regulating the conditions of applying active repentance.